Cisplatin-Induced Eosinophilic Pneumonia. (13th November 2014) - Ideguchi, Hideharu; Kojima, Keisuke; Hirosako, Susumu; Ichiyasu, Hidenori; Fujii, Kazuhiko; Kohrogi, Hirotsugu
Abstract : A 67-year-old man suffering from esophageal cancer was admitted to our hospital complaining of dyspnea and hypoxemia. He had been treated with cisplatin, docetaxel, and fluorouracil combined with radiotherapy. Chest computed tomography revealed bilateral ground-glass opacity, and bronchoalveolar lavage fluid showed increased eosinophils. Two episodes of transient eosinophilia in peripheral blood were observed after serial administration of anticancer drugs before the admission, and drug-induced lymphocyte stimulation test to cisplatin was positive. Thus cisplatin-induced eosinophilic pneumonia was suspected, and corticosteroid was effectively administered. To our knowledge, this is the first reported case of cisplatin-induced eosinophilic pneumonia.